Optimasi Steganografi Berbasis Citra Digital Menggunakan Modifikasi Bit - Lyntom Irfan D; Arief Bramanto Wicaksono Putra; Achmad Fanany Onnilita Gaffar (LPPM UBHINUS MALANG, 2020)
Security and confidentiality are very important aspects for users of information technology. To avoid messages that are sent falling on unauthorized parties and news occurs on the message. There are many ways that can be done for housing data or messages to be sent. One of them is steganography. Steganography is a technique of inserting messages into other media, so that the message will be hidden and what will appear is other media to insert messages. Steganography requires a message and cover. Cover is the medium used to enter messages. This study aims to include a message in the form of an image on the cover in the form of an image in JPG and PNG formats. In this study, using the Least Significant Bit (LSB) method as the insertion method and modification method to optimize the LSB performance in inserting messages of 1 to 4 bits. From the results of research on the insertion with cover images and message images using PNG format based on information and PSNR shows the best number of bits with 1-bit message insertion while in the process of extracting message images from cover images that have gone through the insertion process using PNG format based on cooperation and MAPE shows best bit count with 4 bit message insertion. Decrease, the more bits that are inserted, the quality cover will decrease but the extraction result is the higher the quality increase in the return message.